Environmental complexity of globalization, education, and income inequalities: New insights of energy poverty. (15th March 2022) - Hassan, Syed Tauseef; Batool, Bushra; Zhu, Bangzhu; Khan, Irfan
Abstract: In the coming decades, the energy industry will be confronted with developments related to three significant phenomena: climate change, energy security, and energy poverty. The first two have been widely studied, but less attention has been paid to the third, although it has a significant impact on the lives of millions of people in terms of healthcare, education, environmental concerns, and other socio-economic factors. Therefore, we estimated the effects of energy poverty, education, income inequalities, and globalisation on carbon emissions in BRICS countries between 1989 and 2016. We used continuously updated fully modified and continuously updated biased correction approaches, as well as the common correlated effects mean group and augmented mean group estimators to obtain model estimations that were robust against cross-country dependencies and heterogeneity. The empirical results revealed that economic growth, income inequalities, and energy poverty increased the environmental pressure on BRICS countries. However, the expansion and improvement of education had an impact, directly and indirectly, on the investigated variables and promoted globalisation. Graphical abstract: Image 1 Highlights: This study offers a new insights of energy poverty, education, and globalization. The advanced and reliable panel data technique is employed. Energy poverty significantly intensify the rate of carbon emission. Education and globalization reduce pollution and improve energy poverty.